Design theories and maintenance technologies of slab tracks for high-speed railways in China: a review. Issue 4 (16th November 2021) - Ren, Juanjuan; Deng, Shijie; Zhang, Kaiyao; Du, Wei; Wu, Qinghong
Abstract: The durability and reliability of slab track structures are essential for the long-term safety and stable operation of high-speed railways. In order to provide a solid theoretical basis and technical reference for the advancement of high-speed railway quality, this paper comprehensively discusses design theories of slab track structures, service performance evolution and maintenance technologies, and reviews the innovation happening in the industry. On top of that, the damage evolution, fatigue features and durability of slab tracks, which are highly relevant to serviceability, are summarized, and the future research trend of slab track service behaviours is pointed out. In addition, this paper summarizes the rules of establishing standards for damage maintenance, typical solutions for repairing damage and methods of evaluating the maintenance outcomes that combine field tests and numerical simulations. It also envisions a future direction where advanced testing technologies would assist the evaluation of maintenance effects.